Fostering academic engagement through soft skills and positive emotions: a sustainable development perspective on university education - Wang, Xiaoling; Deng, Xiang; Wan Jaafar, Wan Marzuki; Sulong, Rose Manisah; Zainudin, Zaida Nor; Wan Othman, Wan Norhayati (Frontiers Media SA, 2025)
Introduction: Soft skills, including curiosity, initiative, perseverance, social awareness, adaptability, and leadership, are increasingly recognized as essential for fostering positive emotions and academic engagement in higher education. However, the pathways linking these skills to academic engagement remain underexplored, especially within the Chinese university context. Methods: This study investigated the relationships among soft skills, positive emotions, and academic engagement among 335 undergraduate students (197 females, 58.8%) from four universities in China, across faculties of Education, Literature, and Management. Standardized questionnaires assessing soft skills, positive emotions, and academic engagement dimensions (absorption, dedication, and vigor) were administered. Data were analyzed using SPSS 26 and AMOS 24. Reliability was confirmed through Cronbach's alpha (≥0.70), and construct validity was evaluated via confirmatory factor analysis (CFA). Results: CFA indicated an acceptable to excellent fit for both individual scales and the overall measurement model (χ2/df = 1.887, RMSEA = 0.052, CFI = 0.928). Structural equation modeling (SEM) results supported hypothesized relationships, demonstrating that soft skills directly predicted academic engagement and indirectly predicted it through positive emotions. Positive emotions significantly mediated the relationship between soft skills and all dimensions of academic engagement (absorption, dedication, vigor). Discussion: These findings underscore the importance of developing soft skills and fostering positive emotional experiences to enhance academic engagement. Aligning with sustainable development-oriented educational reforms, the results suggest that comprehensive educational approaches promoting soft skills and emotional well-being can effectively support holistic student growth and sustainable academic success.